Applying the Theory of Consumption Values to Explain Drivers’ Willingness to Pay for Biofuels - Zailani, Suhaiza; Iranmanesh, Mohammad; Hyun, Sunghyup Sean; Ali, Mohd (MDPI, 2019)
The transportation sector has dominated global fuel consumption and as a result, greenhouse gas emissions have risen at an alarming rate. As a consequence, many countries have adopted policies and strategies to diversify their fuel sources in the transportation sector. Biofuel is one of the potential substitution fuels that has attracted the attention of both researchers and policy makers. Public acceptance of biofuels is one of the major challenges for the implementation of biofuel blends in transportation. To determine the influence of different values that affect drivers' willingness to pay for biofuels, the theory of consumption values is applied in the present research. The data were gathered by distributing questionnaires to 343 Malaysian people with driving licences and access to cars. The data were analysed using the partial least squares technique. The results of the analysis revealed that functional values, specific condition, emotional values and novelty seeking were among the main factors that influence drivers' willingness to pay for biofuels. Social values were shown to not be a significant factor. The results of the study contribute to the literature by testing the relationship between consumption values and willingness to pay for biofuels. The information provided in the present research might be beneficial for policy makers in modifying tactics and strategies towards the successful promotion of the usage of biofuels in developing countries.